The Role of Ultrasound in Temporomandibular Joint Disorders: An Update and Future Perspectives - Maranini, Beatrice; Ciancio, Giovanni; Mandrioli, Stefano; Galiè, Manlio; Govoni, Marcello (Frontiers in Medicine, 2022)
Temporomandibular joint (TMJ) disorder is the second most common chronic pain condition affecting general population after back pain. It encompasses a complex set of conditions, manifesting with jaw pain and limitation in mouth opening, influencing chewing, eating, speaking and facial expression. TMJ dysfunction could be related to mechanical abnormalities or underlying inflammatory arthropathies, such as rheumatoid arthritis (RA) or juvenile idiopathic arthritis (JIA). TMJ exhibit a complex anatomy, and thus it is required a thorough investigation to detect TMJ abnormalities. Importantly, TMJ involvement can be completely asymptomatic during early stages of disease, showing no clinically detectable signs, exposing patients to delayed diagnosis and progressive irreversible condylar damage. For the prevention of JIA complications, early diagnosis is therefore essential. Currently, magnetic resonance imaging (MRI) is described in literature as the gold standard method to evaluate TMJ. However, it is a high-cost procedure, not available in all centers, it requires long time for image acquisition, which could represent a problem notably in pediatric population, and it suffers restricted use in patients with claustrophobia. Ultrasonography (US) has emerged in recent years as an alternative diagnostic method, since it is less expensive, not invasive and it does not demand for special facilities. In this narrative review we will investigate US power in TMJ disorders based on most relevant literature data, from early screening of TMJ changes, to differential diagnosis and monitoring. We then propose a potential algorithm to optimize the management of TMJ pathology, questioning which would be the role of ultrasonographic study.